A study of the Lake Baikal level fluctuations on the coastal territories - Olga V. Gagarinova; Tatiana I. Zabortseva (Водное хозяйство России: проблемы, технологии, управление, 2022)
Th e rise of the water level resulted from the construction of the Irkutsk hydro power plant led to flooding, waterlogging, coastal erosion, the formation of new lagoons and estuaries, the transformation of the hydrographic network at the mouths of rivers, and other processes that caused the transformation of coastal geosystems. A possible increase in the amplitude of fluctuations in the lake level due to the development of a new mode of operation of the hydro power plant, as well as the climate change, may lead to new negative consequences for the adjacent coastal territories. Natural components and elements of the socio-economic system of the coastal territories of the lake Baikal, located in the zone of potential influence of fluctuations in the level of the water reservoir, are subject to negative impacts and transformations. Th e processes of flooding and destruction of the shores cause degradation of the soil and vegetation cover, reduction of biological diversity and red book species, loss of unique natural properties of the territory, etc. The influence of fluctuations in the water level is a factor of environmental and socio-economic risks, affecting the livelihoods of the population of the coastal territories of the lake. Baikal. In the economic system of coastal areas, significant losses and damages are possible due to transformations of natural complexes of the coast leading to a decrease in the economic and recreational potentials of the territory. Concurrently the water level fluctuations impact is a factor of environmental and social/economic risks affecting vital activities of the coastal territories’ population.